Utilization of Red Mud as a Source for Metal Ions-A Review - Samal, Sneha (Materials (Basel, Switzerland), 2021)
An overview is presented on the prospective use of red mud as a resource in this review. Various scopes are suggested for the utilization of red mud to maintain a sustainable environment. The potential use of red mud covers the valuable metal recovery that could emphasize the use of red mud as a resource. Red mud could act as reduced slag in the metallurgical field for the extraction of minerals and metals for upscale application. Although many studies have revealed the potential utilization of red mud, most of them are only limited to a lab-scale basis. Therefore, a large-scale investigation on recycling of red mud for the extraction in the area of the metal recovery section will draw attention to the extensive use of red mud. Metal ions of major elements Fe (44 wt.%), Al (18.2 wt.%), Si (14.3 wt.%), Ti (9.3 wt.%), Na (6.2 wt.%), Ca (4.4 wt.%) as major elements and of Mg, V, Mn, Cr, K as minor elements and rare earth elements such as Ce (102 mg/kg), La (56 mg/kg), Sc (47 mg/kg), Nd (45 mg/kg), Sm (9 mg/kg). Moreover, an appropriate in-house metal recovery facility with the alumina industry will come out as a cost-benefit analysis.
Keywords: red mud; reduced slag; mineralogical; metal ion recovery; resources; fly ash